Joint vector sensor beam steering and passive time reversal for underwater acoustic communications - Bozzi, Fabricio (2022)
This paper investigates how to advantageously combine acoustic vector sensor field components for underwater communications. The joint vector sensor beam steering and passive time-reversal receiver structure is proposed and compared against beam steering and standard passive time-reversal separately. The beam steering method takes into account proper directions in order to benefit from highly correlated channels. On the other hand, passive time-reversal was weighted to avoid combinations of possible noisy channels. Performance of receiver structures are quantified using simulation and recorded data from a shallow-water field experiment. In this experiment, a four-element three-dimensional vector sensor array was tied to a drifting ship receiving coherent communication signals from a bottom-moored sound source. Analytical expressions and a numerical simulation based on the experimental acoustic scenario indicate a relationship between source-receiver ranges and the vector sensor channels correlation, providing an initial understanding of the suitability of each receiver structure. Then, using individual or combined vector sensors, such structures were tested with experimental data, where the range relationship hypothesis from the simulation was nearly confirmed. Error analysis shows that shorter ranges favor the beam steering, whereas channel diversity is mostly explored in longer ranges. Furthermore, the proposed joint method, designed for vector sensors, has achieved up to ten times less error than individual approaches, also showing the benefit of exploring beamforming and diversity together.